EFEKTIVITAS PENDIDIKAN DAN PELATIHAN APARATUR SIPIL NEGARA DI DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN MAMUJU TENGAH - Miswar, Adi Putra Miswar; Abdi, Abdi; Wahid, Nur (Universitas Muhammadiyah Makassar, 2024)
Education and training are really needed to improve the performance of ASN in the Central Mamuju Regency Communication and Information Service so that the human resources produced are of high quality and professional in their field. It is hoped that the phenomena seen can improve knowledge, skills and attitudes, thereby creating good quality work at the Central Mamuju Regency Communication and Information Service. The aim of the research is to determine the effectiveness of education and training for state civil servants in the Central Mamuju Regency Communication and Informatics Service and to determine the internal and external factors of education and training for state civil servants in the Central Mamuju Regency Communication and Informatics Service. The method used by researchers is a qualitative method with a descriptive approach and data collection techniques through observation, interviews and documentation. The results of the research show that education and training play a very important role in improving the performance and services of ASN and have been realized well but are not yet optimal, as seen from internal and external factors and also seen from the effectiveness measurement theory according to Richard M. Steers so that employee performance is expected to be able to work. to be better so that it is hoped that it will be able to provide better services to the community.